Barrier to Autointegration Factor (BANF1): interwoven roles in nuclear structure, genome integrity, innate immunity, stress responses and progeria. (June 2015) - Jamin, Augusta; Wiebe, Matthew S
Abstract : The Barrier to Autointegration Factor (BAF or BANF1) is an abundant, highly conserved DNA binding protein. BAF is involved in multiple pathways including mitosis, nuclear assembly, viral infection, chromatin and gene regulation and the DNA damage response. BAF is also essential for early development in metazoans and relevant to human physiology; BANF1 mutations cause a progeroid syndrome, placing BAF within the laminopathy disease spectrum. This review summarizes previous knowledge about BAF in the context of recent discoveries about its protein partners, posttranslational regulation, dynamic subcellular localizations and roles in disease, innate immunity, transposable elements and genome integrity.